Budaya Pesantren: Pengembangan Pembelajaran Turats - Bashori, Bashori; Novebri, Novebri; Salabi, Agus Salim (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2022)
Abstract: Mastering Turat book is one of the competencies of pesantren graduates. However, modernization poses hurdles to pesantren administrators who wish to preserve the tradition of studying Turat literature. Therefore, a custom is required to demonstrate the significance of studying the Turat book. This study aims to investigate, analyze, and provide a model for developing pesantren customs in the context of preserving the Turat legacy. This qualitative study employs a survey and descriptive analysis. The results of the study find that the model for developing the custom of learning the Turat book is implemented in three stages. The first stage is the value reinforcement of using the halaqoh learning paradigm. Secondly, the contribution to the structure and community of the book of Turat learners should be formed. Thirdly, the learners should actively participate in the Turat book contest. Additionally, the modernization of learning activities should take the form of methods and digital libraries. Abstrak: Kompetensi lulusan pesantren salah satunya adalah menguasai kitab turats. Arus modernisasi melahirkan tantangan bagi pengelola pesantren untuk menjaga tradisi pembelajaran kitab turats. Untuk itu diperlukan sebuah budaya sebagai manifestasi nilai pembelajaran kitab turats. Penelitian ini berupaya mengeksplorasi, menganalisis dan menemukan model penciptaan budaya pesantren dalam menjaga tradisi kutubut turats. Penelitian berjenis kualitatif survey deskriptif. Hasil penelitian menunjukkan model penciptaan budaya pembelajaran kitab turats dilakukan melalui serangkaian tahapan. Pertama memperkuat nilai melalui model pembelajaran halaqoh. Kedua membentuk struktur dan komunitas kitab turats. Ketiga aktif mengikuti perlombaan kitab turats. Adapun modernisasi pembelajaran mengarah kepada metode dan perpustakaan digital.